PENDIDIKAN MISI DALAM KONTEKS MULTIKULTURAL DI INDONESIA - Yuni Feni Labobar; Ria Marselin Usmany; Jhounlee Pance Tatuhas (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
Mission is an appreciation for freedom. The author uses the thoughts ofJames A Banks & McgeeBanks Cherry A and J Andew Krik incollaborating on mission and education in a multicultural context inIndonesia. . The type of research used is library research and the methodused is a qualitative analysis of the pluralistic context in Indonesia byusing both theories to analyze the problem. . What needs to be done whenhaving a mission towards pluralism is a dialogical approach to get rid ofall exclusive claims to the truth of one religious tradition.